2022
DOI: 10.1136/gutjnl-2022-327121
|View full text |Cite
|
Sign up to set email alerts
|

Escape from cell-cell and cell-matrix adhesion dependence underscores disease progression in gastric cancer organoid models

Abstract: ObjectiveCell-cell (CC) and cell-matrix (CM) adhesions are essential for epithelial cell survival, yet dissociation-induced apoptosis is frequently circumvented in malignant cells.DesignWe explored CC and CM dependence in 58 gastric cancer (GC) organoids by withdrawing either ROCK inhibitor, matrix or both to evaluate their tumorigenic potential in terms of apoptosis resistance, correlation with oncogenic driver mutations and clinical behaviour. We performed mechanistic studies to determine the role of diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…All 3 CMi IMOs remained sensitive to CC dissociation-induced apoptosis and died upon Y-27632 withdrawal (online supplemental figure 10B). As cell-cell adhesion independence (CCi) was previous observed mostly in advanced stage or diffuse type gastric cancer, 47 their absence in IMOs is consistent with their relatively early stage of neoplastic progression. We did not find any commonly mutated cancer driver genes among the 3 IM spheroids that correlated with the CMi phenotype (figure 6D, online supplemental table 11).…”
Section: Imos With Chromosomal Aberrations Displayed a Cell-matrix Ad...supporting
confidence: 54%
See 1 more Smart Citation
“…All 3 CMi IMOs remained sensitive to CC dissociation-induced apoptosis and died upon Y-27632 withdrawal (online supplemental figure 10B). As cell-cell adhesion independence (CCi) was previous observed mostly in advanced stage or diffuse type gastric cancer, 47 their absence in IMOs is consistent with their relatively early stage of neoplastic progression. We did not find any commonly mutated cancer driver genes among the 3 IM spheroids that correlated with the CMi phenotype (figure 6D, online supplemental table 11).…”
Section: Imos With Chromosomal Aberrations Displayed a Cell-matrix Ad...supporting
confidence: 54%
“…We recently showed that almost all GC organoids were cell-matrix adhesion independent (CMi), while normal gastric organoids were not, suggesting that gaining CMi represents the earliest critical step in malignant transformation. 47 Therefore, we sought to test whether IMOs were CMi by randomly selecting 10 IMOs and 10 AOs/BOs for spheroid formation assay (figure 1A). After 2 weeks in culture, there was a significant growth inhibition, irrespective of the organoid type (figure 7D).…”
Section: Imos With Chromosomal Aberrations Displayed a Cell-matrix Ad...mentioning
confidence: 99%
“… 22 While these adhesive dynamics are vital for normal cell survival, cancer cells often exploit this mechanism to evade apoptosis, highlighting potential therapeutic targets. 23 Our hypothesis was that the downregulation of cell matrix adhesion and developmental growth involved in the morphogenesis of macrophages led to epithelial cell death and morphological changes of OP. Apoptosis of lung alveolar epithelial cells (AECs) is an early pathogenic event in the development of OP, although its causative mechanism is still unclear.…”
Section: Resultsmentioning
confidence: 98%
“…Five studies that provided detailed clinical information on all lines of successful and failed construction of GCOs were further analyzed by different subgroups[ 21 - 27 , 37 ] (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%